Penerapan Terapi Bermain Mewarnai Gambar Dengan Pasir Warna Terhadap Kecemasan Hospitalisasi Anak Usia Prasekolah 3-5 Tahun Di RSUD Pandan Arang Boyolali - Aulia Bintang Kusuma Wardani; Tri Susilowati (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Hospitalization or inpatient care has an impact on anxiety in children. Anxiety or a condition of excessive fear caused by certain situations often occurs in almost every child who is hospitalized or hospitalized. Play activity therapy is a good activity to deal with anxiety in children who experience hospitalization, so that it can accelerate the healing process of pain in children. Determine changes in anxiety levels in preschool aged 3-5 years at RSUD Pandan Arang Boyolali hospital. This study used a descriptive design on two male respondents which was conducted from 4 to 6 July 2023 ar Pandan Arang Boyolali Hospital with each respondent being given intervention for 3 consecutive days. The instrument used was the Spence Children Anxiety Scale SCAS observation sheet to measure the level of anxiety before and after giving therapy. Before the two respondents were put into action, the level of anxiety was moderate (first respondent scored 18; second respondent scored 20), and after the two respondents were put into action, the level of anxiety was mild (first respondent scored 12; second respondent scored 13). The application of play therapy to coloring pictures with color sand is able to reduce anxiety levels in preschool aged 3-5 years at Pandan Arang Boyolali Hospital.